Efficacy and Safety of Catheter‐Based Renal Denervation for Patients With Hypertension: A Systematic Review and Meta‐Analysis - Xiao Chen; Jie Meng; Qiufeng Zhou; Yuehua Ni; Changyang Zuo; Yanfang Zhang (The Journal of Clinical Hypertension)
ABSTRACT This meta‐analysis evaluates the efficacy and safety of renal denervation (RDN) for patients with hypertension. PubMed, EMBASE, the Cochrane Library, and ClinicalTrials.gov were systematically searched to identify relevant studies published before December 31, 2024. Review Manager 5.3 software was used to assess the results of the meta‐analyses and the risk of bias plot. We pooled 2208 participants from 13 studies. The RDN was superior to the sham surgery group in the change in 24 h ambulatory systolic blood pressure (ASBP) and the change in 24 h ambulatory diastolic blood pressure (ADBP) (MD: −4.55 mmHg, 95% CI: −5.65 to −3.44; MD: −2.37 mmHg, 95% CI: −3.06 to −1.68, respectively). For the change in daytime ASBP and ADBP, significant differences were found between the RDN group and the sham group (MD: −6.21 mmHg, 95% CI: −7.61 to −4.80; MD: −2.96, 95% CI: −3.85 to −2.07). Compared to the sham surgery group, the RDN group showed better results in the change in night‐time ASBP and ADBP (MD: −4.67 mmHg, 95% CI: −6.32 to −3.03; MD: −2.28 mmHg, 95% CI: −3.33 to −1.24). No significant differences were found between the RDN group and the sham group in terms of adverse events (AEs) and serious adverse events (SAEs) (p = 0.39 and 0.07). Subgroup analyses showed that RDN remains effective at long‐term follow‐up, and both ultrasound and radiofrequency RDN were effective. Current evidence shows that RDN is an effective treatment for patients with hypertension and does not increase the risk of AEs and SAEs.